ELECTROCHEMICAL DETERMINATION OF KETOROLAC - A NON-OPIOID ANALGESIC AT GLASSY CARBON ELECTRODE - M HANABARATTI, ROHINI; I GOWDA, JAYANT; M TUWAR, SURESH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The study has been carried to investigate the electro-oxidation mechanism and to develop a selective and sensitive method for determination of ketorolac (KTL), a non-opioid analgesic drug,. Methods: A simple electro analytical method was used for the determination of ketorolac (KTL) using glassy carbon electrode by cyclic and differential pulse voltammetric techniques (DPV). The effect of various experimental parameters such as accumulation time, pH, scan rate, on the voltammetric responses of KTL was evaluated. Results: In the optimized conditions, variation of peak current with respect to concentration was studied and the calibration curve of the peak current vs. KTL concentration was drawn with a linear range of 10- 350 Î¼M with an excellent detection limit of 8.08Ã—10-8 M. This method was successfully tested for the determination of KTL in pharmaceuticals and human urine samples. Conclusion: From the results, it was observed that, the selected method is rapid, sensitive and low cost.